An Effective Treatment for Tinnitus and Hyperacusis Based on Cognitive Behavioral Therapy in an Inpatient Setting: A 10-Year Retrospective Outcome Analysis - Nolan, Daniele R.; Gupta, Rahul; Huber, Christian G.; Schneeberger, Andres R. (Frontiers in Psychiatry, 2020)
AIM: Tinnitus is a phenomenon with a considerable prevalence in the general population, leading to high levels of suffering. It is a symptom that can present itself comorbidly with a variety of psychiatric and medical illnesses. We established a treatment of tinnitus, which is based on a multimodal approach including a specific cognitive-behavioral therapy (CBT) method in an inpatient setting. This approach includes education on tinnitus, applying coping strategies and techniques of relaxation, directed attention and music therapy. We aim to evaluate the efficacy of this treatment approach. MATERIAL / METHODS: We included retrospective data of 268 patients that underwent tinnitus treatment throughout the ten-year existence of the treatment program. We assessed routine clinical data pre and post treatment with parameters concerning tinnitus-distress, hyperacusis and psychological well-being. To determine these variables we used validated instruments including the Tinnitus Questionnaire (TQ), Questionnaire on hypersensitivity to sound (QHS), Brief Symptom Inventory (BSI) and the Beck Depression Inventory (BDI-II). RESULTS: Patients showed highly significant reduction in all of the examined clinical outcomes. Reduction of TQ, the primary outcome measure, was 15.39 (SD 21.88) from a mean baseline value of 35.72 (p<0.001). The QHS showed a reduction of 6.72 (SD 8.23) from a mean baseline value of 18.98 (p<0.001). Moreover, psychological strain was also reduced with high significance, as illustrated in reduction of BSI and BDI-II; reduction in BSI from 49.63 by 24.41 (SD 26.88; p<0.001) and BDI-II from 16.89 by 7.47 (SD 8.76; p<0.001). DISCUSSION: The multimodal treatment program for tinnitus, including a specific CBT method proves to be a highly effective means of significantly reducing not only tinnitus and hyperacusis, but also distress related to tinnitus. Furthermore it also enables considerable reduction of concomitant psychiatric symptoms such as depression. CONCLUSIONS: Our results underline the importance of intensive and multimodal approaches to the treatment of tinnitus.